নীরব দেশত্যাগ, হুন্ডি ও অভিবাসন - রশীদ, মামুন (ঢাকা : আগামী প্রকাশনী, 2015)
Articles on economic condition of Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Economics; Bangladesh -- Economic conditions